Analysing The Implementation Of The Subsidy Reinvestment And Empowerment Programme (Sure-P) On Rural Communities: A Case Study Of Six Local Governments In Niger State, Nigeria - Jibrin, Abubakar Mohammed (2025)
This research aims to analyze the impact of the implementation of Subsidy Reinvestment and Empowerment Programmes (SURE-P) on rural communities, focusing on six selected Local Governments Areas of Niger State, Nigeria